Analisis Faktor Perilaku Pembelian Bisnis terhadap Pasar Bisnis - Sallimah Ika Putri Malau; Nuri Aslami (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
The motivation behind Marketing is to satisfy and give fulfillment to the requirements and wants of shoppers. Customer conduct is the investigation of how people, gatherings and associations pick, purchase, use, make products, administrations, thoughts, or encounters to fulfill their needs and needs. Giving fulfillment to buyers gives directions to improving or presenting items or administrations, deciding costs, building up circulation channels, planning messages, and creating other promoting exercises. Advertisers are dependably keeping watch for arising patterns that give new promoting openings. In the business market, contest will emerge with numerous makers offering their items and administrations to shoppers. Rivalry in the business world is progressively energetic in this day and age, worldwide promoting causes organizations to need to attempt how to have the option to rival different organizations that are contenders. Keywords : Business Market, Consumer, Consumer Behavior